2015
DOI: 10.20870/oeno-one.2015.49.1.94
|View full text |Cite
|
Sign up to set email alerts
|

Sufficiency ranges (sr) and deviation from optimum percentage (dop) references for leaf blade and petiole analysis in ‘Red Grenache’ grapevines

Abstract: <p class="BodyTextIndent" style="text-align: justify;"><strong>Aim</strong>: To obtain specific references for the nutritional diagnosis of ten essential nutrients for leaf blade and petiole of ‘red Grenache’ (<em>Vitis vinifera</em> L.).</p><p class="BodyTextIndent" style="text-align: justify;"><strong>Methods and results</strong>: Leaf blades and petioles from 36 vineyards of ‘red Grenache’ (<em>Vitis vinifera</em> L.) grafted on Richter 110 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Enzyme activity was also affected by the treatments. In terms of the effect of the organic materials used in this study on dehydrogenase enzyme activity in soils, the application of P+(PR+FM) in 2017 and of Jones et al (1991) and Benito et al (2015). PR+FM in 2018 yielded the highest figures.…”
Section: Microbiological and Biochemical Characteristics Of The Soilmentioning
confidence: 82%
See 4 more Smart Citations
“…Enzyme activity was also affected by the treatments. In terms of the effect of the organic materials used in this study on dehydrogenase enzyme activity in soils, the application of P+(PR+FM) in 2017 and of Jones et al (1991) and Benito et al (2015). PR+FM in 2018 yielded the highest figures.…”
Section: Microbiological and Biochemical Characteristics Of The Soilmentioning
confidence: 82%
“…When comparing the values obtained from all treatments with the limits for the full flowering period, (according to Jones et al (1991) and Benito et al (2015)), the amounts were found to be high for nitrogen, optimal-high for phosphorus, optimal for calcium and Mg and low for potassium (Table 5). Fe and Mn were evaluated as being optimal and zinc values as being low (Table 6).…”
Section: Leaf Macro and Micro Nutrientsmentioning
confidence: 90%
See 3 more Smart Citations